If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3b-2=4(b-1)+2b
We move all terms to the left:
3b-2-(4(b-1)+2b)=0
We calculate terms in parentheses: -(4(b-1)+2b), so:We get rid of parentheses
4(b-1)+2b
We add all the numbers together, and all the variables
2b+4(b-1)
We multiply parentheses
2b+4b-4
We add all the numbers together, and all the variables
6b-4
Back to the equation:
-(6b-4)
3b-6b+4-2=0
We add all the numbers together, and all the variables
-3b+2=0
We move all terms containing b to the left, all other terms to the right
-3b=-2
b=-2/-3
b=2/3
| 10x-6x+6-3=19 | | 2+4r=-1+r | | 12=-3(x+1)+8x | | 2x=(320/28 | | 2x=(320/2) | | H(t)=-4t^2+32t+1 | | x^2=−16 | | 6(x+7=114 | | w/2=1 | | -3t÷-8=25 | | (2a)^10a=10 | | 4n-1=63 | | (1/3)x+(2/5)=4(15)+(3/5)x-(2/3) | | 8(x+7)=7(×-7) | | a=2*3.14*8(8+12) | | x/4+4=6x+8 | | X+3+x-1=x+1+x+3+x+5 | | 0.33x+0.4=0.26+0.6x-0.6 | | 1/3y=y*3 | | -3x+3=13 | | 4x+11=8x-8 | | 9/6=x/9.3 | | 6=-s=77 | | 6x^2-39x-18=0 | | 9x^2+12=48 | | 0,75t=1,4 | | k^2−7k+12.25=0 | | 5b-3=3(b+7)+3b | | 10/x=20/10 | | d*d+3=67 | | 0.6+0.75*t=2 | | 2y2=2πy |